2021
DOI: 10.3389/fbioe.2021.662598
|View full text |Cite
|
Sign up to set email alerts
|

Screening For Yeast Phytase Leads to the Identification of a New Cell-Bound and Secreted Activity in Cyberlindnera jadinii CJ2

Abstract: Phytic acid is an anti-nutritional compound able to chelate proteins and ions. For this reason, the food industry is looking for a convenient method which allows its degradation. Phytases are a class of enzymes that catalyze the degradation of phytic acid and are used as additives in feed-related industrial processes. Due to their industrial importance, our goal was to identify new activities that exhibit best performances in terms of tolerance to high temperature and acidic pH. As a result of an initial scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The optimum temperature for phytase activity in Cyberlindnera jadinii CJ2 was found to be 50°C with a highest activity of 51.95 mU/mgdw, while the activity decreased with increase in temperature (24). Capusoni et al, (24) have shown pH 4.5 as optimum for highest phytase activity by Cyberlindnera jadinii CJ2. According to Alves et al, (25) Muscodor sp.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The optimum temperature for phytase activity in Cyberlindnera jadinii CJ2 was found to be 50°C with a highest activity of 51.95 mU/mgdw, while the activity decreased with increase in temperature (24). Capusoni et al, (24) have shown pH 4.5 as optimum for highest phytase activity by Cyberlindnera jadinii CJ2. According to Alves et al, (25) Muscodor sp.…”
Section: Discussionmentioning
confidence: 93%
“…In another study, 50°C was shown to be an appropriate temperature for a bacterial strain named DR 6 to produce 387 U/ml of phytase (9). The optimum temperature for phytase activity in Cyberlindnera jadinii CJ2 was found to be 50°C with a highest activity of 51.95 mU/mgdw, while the activity decreased with increase in temperature (24). Capusoni et al, (24) have shown pH 4.5 as optimum for highest phytase activity by Cyberlindnera jadinii CJ2.…”
Section: Discussionmentioning
confidence: 94%
“…Cyberlindnera jadinii CJ2 Cell bound Capusoni et al 96 Finarome sp. Cell bound Klosowski et al 97 Pichia kudriavzevii Cell bound Hellstrom et al 98 Pseudomonas strains Cell bound Zhuang et al 99 Bacillus subtilis P6 Intracellular Trivedi et al 100 Talaromyces purpureogenus NSA20 Intracellular Ahmed et al 101 Pediococcus acidilactici SMVDUDB2 Intracellular Bhagat et al 102 Pseudomonas mandelii GS10-1 Extracellular Li et al 103 Bacillus licheniformis Extracellular Dan et al 104 Pediococcus pentosaceus KTU05-8, KTU05-9 Extracellular Cizeikiene et al 105 Lactic acid bacteria Extracellular Nuobariene et al 106 Lactobacillus fermentum spp.…”
Section: Microorganisms Site Referencesmentioning
confidence: 99%
“…D. hansenii is able to grow using phytic acid as a sole phosphorus source [45]. To characterize phytase activity in the Mo40 strain, we started sequencing the gene encoding in order to compare a marine phytase sequence with its terrestrial counterpart (reference strain CBS 767, isolated from beer [46]).…”
Section: Phytase Activitymentioning
confidence: 99%